PRODUCTION OF SECONDARY METABOLITES AND FORMULATION OF NANO SPRAY GEL RED GINGER (Zingiber officinale var.rubrum) FERMENTATION EXTRACT AS ANTIINFLAMATION - Ni Wayan Rika Kumara Dewi; Made Dwike Swari Santi; Kusdiharti, Meutia Sri (LPPM STIKES BULELENG, 2025)
Red ginger (Zingiber officinale var.rubrum) has active compounds, namely gingerol and shogaol which provide anti-inflammatory activity. The purpose of this study was to improve the quality and quantity of secondary metabolites in red ginger extract through the fermentation process, as well as the development of nanoparticle technology in the formulation of natural pharmaceutical preparations in the form of nano spray gel as an anti-inflammatory. This research method is a true experimental laboratory, with a fermentation process using Trichoderma harzianum mold. Active compounds were analyzed using GCMS. In vitro, anti-inflammatory activity was tested using the protein denaturation method, negative control using bovine serum albumin, and positive control using sodium diclofenac (KP). Anti-inflammatory activity was tested on red ginger extract (EJM), red ginger fermentation extract (EFJM), nano spray gel (SNSG) preparations with active ingredients EFJM at F0 ; F1 ; F2 ; F3 ; and F4. The results showed an increase in yield after fermentation, from 8.03% to 14.3%. The active compounds analyzed also experienced an increase in the % area of abundance in the 6-gingerol compound from 1.23% to 5.43% and the 6-shogaol compound from 5.25% to 13.36%. The results of the anti-inflammatory activity test on SNSG F4 had an anti-inflammatory inhibition % of 89.35% at a concentration of 125 ppm. The IC50 value of all treatments obtained data EFJM> EJM> KP Nadik> F4> F2> F3> F1> F0. That Shows is a red ginger fermentation extract as an active ingredient in nanospray gel preparations can provide strong anti-inflammatory activity.